2018
DOI: 10.1039/c8py00862k
|View full text |Cite
|
Sign up to set email alerts
|

Aromatic polyesters from biosuccinic acid

Abstract: Biosuccinic acid, obtainedviasugar fermentation, is cyclodimerized and oxidized to yield building blocks for aromatic polyesters with high glass transition temperatures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 41 publications
0
29
0
Order By: Relevance
“…38 It is noteworthy that various biorenewable polyesters with alternating aromatic/aliphatic units bearing ether-linkages have been developed by Miller and coworkers. [39][40][41] They indicated that the thermal properties of the biobased polymers are readily tuneable because of an adequate combination of so and hard segments in the main chain. In particular, the use of ferulic acid and p-coumaric acid as aromatic components contributed to improvements in glass transition temperature (T g ).…”
Section: Introductionmentioning
confidence: 99%
“…38 It is noteworthy that various biorenewable polyesters with alternating aromatic/aliphatic units bearing ether-linkages have been developed by Miller and coworkers. [39][40][41] They indicated that the thermal properties of the biobased polymers are readily tuneable because of an adequate combination of so and hard segments in the main chain. In particular, the use of ferulic acid and p-coumaric acid as aromatic components contributed to improvements in glass transition temperature (T g ).…”
Section: Introductionmentioning
confidence: 99%
“…Polyesters made from terephthalic acid and aliphatic diols such as polyethylene terephthalate (PET) and polybutylene terephthalate (PBT) constitute a class of versatile engineering plastics . Because we have succeeded the development of terephthalates showing efficient solid‐state blue fluorescence, we envisioned that polyesters consisting of dialkyl 2,5‐dialkoxyterephthalate framework could be efficient blue fluorescent polymers in the neat films . Because we observed that the quantum yields of 2 ba were higher than those of 2 aa (Table ), we chose an isopropoxy group as the alkoxy group.…”
Section: Resultsmentioning
confidence: 99%
“…Various natural, eco-friendly chemical structures have been produced and used after several modifications of their chemical function to access sustainable and eco-friendly polymers. These include vanillin [29] or bio-succinic acid [30] for semi-aromatic polyesters, lignins for phenolic oligomers [31], epoxidized castor oils for thermosetting architectures [32], catechol-based moieties for highly adhesive polymers [33], biodegradable copolymers from SO2, renewable eugenol for biodegradable materials [34] or cashew nut shell liquid for various systems [35].…”
Section: Bio-based Polyimidesmentioning
confidence: 99%